Feasibility and Efficacy of Cardiopulmonary Rehabilitation After COVID-19. (October 2020) - Hermann, Matthias; Pekacka-Egli, Anna-Maria; Witassek, Fabienne; Baumgaertner, Reiner; Schoendorf, Sabine; Spielmanns, Marc
Abstract : Abstract: The COVID-19 pandemic affects a large number of patients with a rapid progression of respiratory failure often requiring hospitalization or intensive care unit treatment in some patients. Survivors of severe COVID-19 experience persistent weakness and cardiorespiratory failure. Feasibility and potential benefit of cardiopulmonary rehabilitation after COVID-19 remains unclear. Therefore, we retrospectively analyzed a cohort of COVID-19 patients in a single-center inpatient rehabilitation clinic and describe performance and outcome during cardiopulmonary rehabilitation. Patients were referred from acute care hospitals for rehabilitation after severe COVID-19. The cohort ( N = 28) was divided in ventilated or not ventilated patients for further analysis. Fifty percent were female, the mean age was 66 yrs, and patients stayed in the acute hospital for 19.3 ± 10.7 days before referral for cardiopulmonary rehabilitation. Seventeen patients (61%) needed previous intensive care unit treatment in the acute care hospital. Risk factors, assessments, and questionnaires on admission were comparable in both groups. Significant enhancements were observed in 6-min walking test and feeling thermometer, which were independent of previous ventilation status. In conclusion, comprehensive cardiopulmonary rehabilitation after COVID-19 is safe, feasible, and effective. Improvements in physical performance and subjective health status were independent of previous ventilation.